2016
DOI: 10.1177/0961463x16656854
|View full text |Cite
|
Sign up to set email alerts
|

‘Running out of time’: Exploring the concept of waiting for people with Motor Neurone Disease

Abstract: Waiting is a part of everyday life. It is often characterised by its banality: its quotidian nature. Time spent waiting can be seen as boring, wasted, and at times painful or distressing, or conversely hopeful or full of potential. The experience of Motor Neurone Disease (MND) reveals a population for whom (limited) time has a significant impact on quality of life. This paper will argue that waiting, for people with MND, exemplifies the relationship between time, power and agency. In so doing we can better con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The subjective experience of waiting has generally been described as one that is negative, associated with feelings of powerlessness, hopelessness, frustration and disappointment, particularly in the case of lengthy or chronic waits (Auyero, 2011; Schwartz, 1975), although the potential for waiting to be experienced as a hopeful time that is potentially both active and productive has not been discounted (Ferrie and Wiseman, 2016; Rotter, 2016). Waiting can also be regarded as an essential feature of working life, since a working day with no pauses would be experienced as overly intense and draining.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The subjective experience of waiting has generally been described as one that is negative, associated with feelings of powerlessness, hopelessness, frustration and disappointment, particularly in the case of lengthy or chronic waits (Auyero, 2011; Schwartz, 1975), although the potential for waiting to be experienced as a hopeful time that is potentially both active and productive has not been discounted (Ferrie and Wiseman, 2016; Rotter, 2016). Waiting can also be regarded as an essential feature of working life, since a working day with no pauses would be experienced as overly intense and draining.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of waiting in other literatures across the social sciences can be linked with the organisational temporality literature to show that the subjective experience of waiting, especially chronic, long-term waiting, may be associated with feelings of powerlessness and a limited sense of agency (Ferrie and Wiseman, 2016; Liang, 2017). For example, Griffiths (2014) found that the waiting experienced by refused asylum seekers and detainees led to disrupted temporalities and engendered feelings of instability and precarity.…”
Section: Waiting and Temporalitymentioning
confidence: 99%
See 2 more Smart Citations
“…This corresponds with research by Broom et al (2018) on cancer and waiting. Similarly, in their research with individuals with motor neurone disease, Ferrie and Wiseman (2016) posit that while waiting is often constructed as negative, they cite the hope it can sometimes invoke, a hope that is absent when illness is terminal. They go on to argue that in terminal illness, waiting (for treatment, deterioration) ‘challenges the idea of waiting as ambivalent and banal’ (Ferrie & Wiseman, 2016, p. 538).…”
Section: Resultsmentioning
confidence: 99%